MATHEMATICS SPATIAL ANALYSIS FOR OPTIMIZATION THE FIRE FIGHTING STATION PLACEMENT IN SOUTH JAKARTA, INDONESIA - Ngarap Imanuel Manik; Maryuri Septreziera; Deshinta Puspa Ayu Dwi Argaswari (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2022)
This research aims to apply the spatial analysis to optimize the placement of firefighting units in the area of South Jakarta. The calculation and pre-analysis shown that there are some uncovered service areas at South Jakarta. Therefore, the recalculation and analysis help to find out the strategic new possible location for the fire station. Optimalization of the location of the new fire station is conducted by calculating the minimum time travel from help point to fire point. Other than that, the minimum time travel also calculated based on actual blocks and crowd. After that, the optimizing the location of the fire unit is determined by the support of a planning tool known as ArcView. It is a Geographic Information System (GIS) through the formulation of a mathematical and accessibility model. Through the new analysis with considering the actual fact and using the technology, the results showed that to optimize of the entire range of the South Jakarta area another ten new posts of firefighting unit need to be added.